Implementation of Food Estate for Improving The Community Welfare from The Perspective of Agrarian Reform in Indonesia - Nabella, Nabella Rezkika; Haq, Muhammad Izzul (UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to analyze the implementation of food estates in improving community welfare from an agrarian reform perspective. Additionally, it seeks to identify the obstacles to implementing food estates in enhancing community welfare. A food estate aims to achieve food security for improving community welfare. In Bansari Subdistrict, Temanggung Regency, Indonesia, the Food Estate program utilizes existing land for horticulture without opening new land. However, in a broader context, several issues regarding this program have led to it being considered less implementable and potentially contradictory to the concept of welfare from an agrarian reform perspective. Answering the problem, this field study employed an empirical legal approach and theories of natural resource management, legal benefit theory, and welfare theory. The results show that implementing food estates in Bansari District, Temanggung, has improved community welfare from an agrarian reform perspective. One of the reasons for the program's success is that it is targeted and does not open new land, taking into account aspects of nature conservation and sustainability of benefits for farmer groups. The challenges faced by the food estate in Bansari District, Temanggung Regency, include internal conflicts among farmer groups due to poor communication, imbalances in the implementation of the food estate program, and a lack of information regarding data on farmer groups receiving subsidies from the food estate program.